2012
DOI: 10.3758/s13423-011-0203-9
|View full text |Cite
|
Sign up to set email alerts
|

Working memory capacity modulates habituation rate: Evidence from a cross-modal auditory distraction paradigm

Abstract: Habituation of the orienting response is a pivotal part of selective attention, and previous research has related working memory capacity (WMC) to attention control. Against this background, the purpose of this study was to investigate whether individual differences in WMC contribute to habituation rate. The participants categorized visual targets across six blocks of trials. Each target was preceded either by a standard sound or, on rare trials, by a deviant. The magnitude of the deviation effect (i.e., prolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 32 publications
9
57
1
Order By: Relevance
“…[27] Further, the recovery from attentional capture seems to depend partly on individual differences in working memory capacity, too: Participants with greater cognitive control abilities showed an increased habituation rate. [28] From an interference-by-process perspective [16,29] the disruptive effect of a distractor increases with the degree to which it competes for action. While at first sight the absence of a self-relevance effect seems to be inconsistent with such an idea, this might simply be due to the nature of the task.…”
Section: Discussionmentioning
confidence: 99%
“…[27] Further, the recovery from attentional capture seems to depend partly on individual differences in working memory capacity, too: Participants with greater cognitive control abilities showed an increased habituation rate. [28] From an interference-by-process perspective [16,29] the disruptive effect of a distractor increases with the degree to which it competes for action. While at first sight the absence of a self-relevance effect seems to be inconsistent with such an idea, this might simply be due to the nature of the task.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrating a relationship between auditory attention and WM capacity have employed complex span measures of capacity (Sörqvist et al, 2012; Tsuchida et al, 2012; Colflesh & Conway, 2007; Conway et al, 2001), which tap memory retrieval skills in addition to capacity (Unsworth & Engle, 2007b). Here, we employed a measure of WM that was previously shown to be robust to individual differences in strategy use (Vogel et al, 2001) and highly predictive of the degree of focus of an individual’s “spotlight” of visual spatial attention (Fukuda & Vogel, 2009, 2011) as well as performance on standard measures of fluid intelligence (Fukuda, Vogel, Mayr, & Awh, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Conway and colleagues found that individuals with higher WM spans were less likely to detect their own name in an unattended auditory channel (Conway, Cowan, & Bunting, 2001), but this effect was reversed when participants were clued to the possible presence of their name (Colflesh & Conway, 2007). Additionally, Sörqvist and colleagues have reported relationships between span scores and auditory attention during concurrent memory tasks (Sörqvist, Nöstl, & Halin, 2012; Sörqvist, Stenfelt, & Rönnberg, 2012; Sörqvist, 2010). A recent ERP study reported that greater reading span performance correlated with reduced auditory N1 amplitude evoked by distractors in an oddball task, but N1 amplitudes were also reduced for targets, making it unclear whether these effects reflected enhanced control of auditory attention or a more general mechanism such as arousal (Tsuchida, Katayama, & Murohashi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with high working memory capacity ( WMC), as measured by complex-span tasks that tap into a domaingeneral construct (Kane et al, 2004), are more able to divide attention across multiple channels (Colflesh & Conway, 2007) and more able to maintain focus in selective attention situations (Kane, Bleckley, Conway, & Engle, 2001) in comparison with their low capacity counterpart. Furthermore, high-WMC individuals are less susceptible to auditory distraction in visual-verbal task settings (Sörqvist, Nöstl, & Halin, 2012) as well as in auditory-verbal task settings (Sörqvist & Rönnberg, 2012;Stenfelt & Rönnberg, 2009;Rönnberg, Rudner, Foo, & Lunner, 2008;Conway, Cowan, & Bunting, 2001). Findings such as these suggest that individuals with a large pool of central cognitive resources (i.e., high WMC) have superior attention abilities and have led some theorists to argue that WMC is equivalent to the capacity of attention (Cowan, 2005).…”
Section: Introductionmentioning
confidence: 99%